The Effectiveness of Jigsaw Learning Model by Using Numbered Cards: Strategy for Increasing Mathematics Learning Motivation Students in Elementary School - BK, Muh. Khaerul Ummah; Hamna, Hamna (Institut Agama Islam Negeri Palopo, 2021)
This study aims to increase the motivation of learning mathematics in elementary school through the implementation of the Jigsaw learning model based on the use of numbered cards as an effective strategy to increasing students’ motivation to learn mathematics by involving research samples of 52 students. this study analyzed using a descriptive quantitative approach with Quasi Experiment Nonequivalent Control Group Design. Collecting research data using instruments such as teacher and student observation sheets and questionnaire instruments that have been validated by expert validators. The results of this study indicate that the students’ motivation in the experimental class is better than the control class, with evidence that there has been an increase in the learning process which has an impact on increasing students’ motivation to learn mathematics consistently from the first meeting to the third meeting with the good assessment categories. the results of this study are that the use of numbered cards makes it easier to organize students’ group learning activities through the implementation of the Jigsaw learning model, stimulates the development of students learning concentration, and is even more enthusiastic for students to be actively involved in completing their learning tasks.